THE INFLUENCE OF PROFITABILITY (ROA), SOLVENCY (DAR), COMPANY AGE, AUDIT FEE, AND ACCOUNT SIZE ON AUDIT DELAY : (EMPIRE STUDY ON NON-CYCLICAL CONSUMER SECTOR LISTED IN INDONESIAN STOCK EXCHANGE 2019-2021) - Devi Febriana; Z, Rico Wijaya; Jumaili, Salman (Jambi Accounting Review (JAR), 2023)
This study aims to empirically prove the influence of profitability, solvency, company age, audit fees and KAP size on audit delay. This research is quantitative research using secondary data obtained from the company's annual report. The population in this research is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange from 2019-2021. The number of samples used in this research was 135 data. The data analysis technique used is multiple linear regression analysis with the software used for data processing is SPSS version 25. Based on the results of the analysis it is known that simultaneously the variables profitability, solvency, company age, audit fees and KAP size influence audit delay, while partially The solvency variable has a significant effect on audit delay, while the profitability variables, company age, audit fees and KAP size partially have no effect on audit delay.